Parental Perception of Fever in Children - Al-Khalidy, Mohammed , J; Thaher, Mahmood; Abdul Hameed, Ban (AL-Kindy College Medical Journal, 2007)
Back ground : Fever is a common medical problem inchildren. parents have been shown unrealistic fears ofharmful effects of fever in their children. Resulting ininappropriate management of fever in their children.Objective: the objective of this study was to surveyparents about their knowledge andattitude concerning feverin their children.Methods : The study involved random selection ofparents who brought their febrile children to emergencydepartment or out-patient clinics of five teaching and nonteaching hospitals in Baghdad from first of October to endof December 2002.Parents of 400 febrile children were interviewed using astandard questionnaire to obtain sociodemographicinformation and current knowledge of fever.Results: Approximately 69% of the respondents werefemale, 68% their age was in the range of 21-35 years.Seventy seven percent of parents had two or more children.More than 70% of parents demonstrated a poorunderstanding of definition of fever , maximumtemperature of untreated fever and threshold temperaturerequiring antipyretics . Twenty sevev percent of parentsconsidered temperature less than 38.0 coto be fever,another 27% did not know, the definition of fever, 61% feltthat temperature of less than 40,0 cocould be dangerous toa child, and 27% could not define high fever. Another 28%believed that if left untreated, temperature could rise to42.0 coor higher, but 39% could not provide an answer,and about 60% did not know the minimum temperature foradministering antipyretics. And 60% did not know theminimum temperature for bathing , or sponging.Approximately 93% of parents demonstrated fear ofconsequent body damage from fever , including convulsion,brain damage ,coma, blindness and even death.Conclusion: parental misconception about fever reflectsthe lack of active health education. Health professionalshave apparently not done enough to educate parents on thiscommon medical problem and it,s consequences